THE CONCEPT OF REVELATION IN SARVEPALLI RADHAKRISHNAN AND H. RICHARD NIEBUHR - Austin B Creel (Journal of Dharma, 1978)
A promising arena for comparative work in religious studies is the understanding of "religion" in different traditions. Toward that end, the concept of revelation in Hinduism and Christianity may be an illuminating investigacion, particularly as expressed in the thought of two outstanding modern spokesmen, Sarvepalli Radhakrishnan and Helmut Richard Niebuhr. In such a study it should not be forgotten, however, that the term revelation is of Western, not Indian, provenacce, and to the extent that laGguagc is constitutive of interpretacion, there may be conceptual difficulties of considemble magnitude in making such a comparative study. To be sure, Radhakrishnan’s usage of the term seems clearly to authorize a study of the concept of revelation in his perspective, and thus such an article in English seems to be a virtually harmless undertaking. But if one asks what Sanskrit word or words are behind Radhakrishnan’s presentation of revelation (a matter on which I do not believe he comments), some disturbing questions about the appropriateness of the inquiry arise. Keeping that in mind, but holding it in abeyance, what understanding of revelation appears in the writings of Radhakrishnan and Niebuhr?